Prevalence and Correlation of Anxiety, Insomnia and Somatic Symptoms in a Chinese Population During the COVID-19 Epidemic - Huang, Yuanyuan; Wang, Yanxia; Zeng, Lingyun; Yang, Jiezhi; Song, Xiuli; Rao, Wenwang; Li, Hehua; Ning, Yuping; He, Hongbo; Li, Ting; Wu, Kai; Chen, Fengjuan; et al. (Frontiers in Psychiatry, 2020)
Background: Anxiety has been a common mental state during the epidemic of Coronavirus Disease 2019 (COVID-19) and is usually closely related to somatization. However, no study on somatization in anxiety and its relationship with insomnia has been conducted. Therefore, this study aimed to identify the prevalence of anxiety, somatization and insomnia and explore the relationships between different psychological states in the general population during the COVID-19 outbreak. Methods: A total of 1172 respondents were recruited from 125 cities in mainland China by an online questionnaire survey. All subjects were evaluated with the 7-item Generalized Anxiety Disorder (GAD-7) scale, the somatization subscale of the Symptom Checklist 90-Revised (SCL-90-R) and the 7-item Insomnia Severity Index (ISI). Results: The percentages of anxiety, somatization and insomnia were 33.02%, 7.59% and 24.66%, respectively. The prevalence of somatization was 19.38% in participants with anxiety. Compared to the anxiety without somatization group, the anxiety with somatization group had a significantly higher percentage of patients with a history of physical disease and insomnia, as well as higher GAD-7 scores and SCL-90 somatization subscores (all p < 0.001). The SCL-90 somatization subscores were positively correlated with age, history of physical disease, GAD-7 scores, and ISI scores (all p < 0.001). Furthermore, multivariate logistic regression showed that GAD-7 score, ISI score and age were risk factors for somatization in the anxious population. Conclusions: Somatic and psychological symptoms were common in the general population during the COVID-19 outbreak. Somatic symptoms, anxiety and insomnia are closely related, and improving anxiety and sleep quality may help relieve somatic symptoms.